Antibacterial activities, chemical composition, and efficacy of green extract Carica papaya peel on food model systems - Abdullah Sani, Muhamad Shirwan; Mohamad Asri, Nurul Aimi Amanina; Othman, Rashidi; Nordin, Noor Faizul Hadry; Mohd Desa, Mohd Nasir (IIUM Press, 2022)
This study investigated anti-bacterial activities, chemical composition, and extract efficacy of Carica papaya peel (CPPE) var. Sekaki/Hong Kong. Nine green solvents were used to extract the Carica papaya peel, and the extracts were subjected to anti-bacterial tests and assays against 14 bacteria. The most potent extract was then subjected to phenolic and flavonoid assays, gas chromatography-mass spectrometry (GC/MS) analysis, and efficacy study on food model systems. All CPPEs showed anti-bacterial activities, and pentane extract had moderate to high anti-bacterial activities against all 14 bacteria. Ethanol extract of Carica papaya peel (ECPPE) inhibited C. perfringens, L. monocytogenes, B. subtilis, V. parahaemolyticus, and V. vulnificus with a minimum inhibitory concentration (MIC) of 1.563 mg/ml; therefore, the ECPPE was selected as the most potent extract. The total phenolic (TPC) and flavonoid contents (TFC) of the CPPEs ranged between 6.20 to 58.75 mg GAE/g DW and 1.35 - 29.09 mg QE/g DW, respectively. Palmitic acid, linoleic acid, β-sitosterol, and stigmasterol in ECPPE may be potential anti-bacterial compounds that render anti-bacterial activities. This study evaluated the ECPPE effectiveness on carbohydrate, protein, fat, and fibre model systems via optical density measurement against C. perfringens, L. monocytogenes, B. subtilis, V. parahaemolyticus, and V. vulnificus. The result showed that the ECPPE could effectively inhibit the tested bacteria in low carbohydrate and high protein, fat, and fibre food model systems.